ON SOME ASPECTS OF THE EVOLUTION OF NONCONVENTIONAL TECHNOLOGIES IN THE LAST DECADE - Dumitru Mnerie; Mihail Aurel Titu; Gabriela Victoria Mnerie (Nonconventional Technologies Review, 2025)
The historical beginning of nonconventional technologies in Romania can be appreciated as the year 1954, when the Institute of Electrotechnical Research, created under the auspices of the Ministry of Electric Energy, was established in Timisoara. That's when the foundations were laid for the creation of the first Electrotechnologies laboratory in Romania at the Department of mechanical technologies (TM), UP Timisoara. After 20 years, the Center for Research in Nonconventional Technologies was established at the "Traian Vuia" Polytechnic Institute in Timisoara. In this paper, some references are made on the evolution of nonconventional technologies in Romania, with an emphasis on some developments from the last 10 years. Some novelties regarding modern applied technologies, based on energy concentration, such as 3D printing using metal powders, ultrasonic welding, are addressed in more detail. Some registered and certified invention patents in the field of nonconventional technologies are also recorded.